2016
DOI: 10.1007/s13311-016-0453-3
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinations for Neuroinfectious Disease: A Global Health Priority

Abstract: Vaccines for neuroinfectious diseases are becoming an ever-increasing global health priority, as neurologic manifestations and sequelae from existing and emerging central nervous system infections account for significant worldwide morbidity and mortality. The prevention of neurotropic infections can be achieved through globally coordinated vaccination campaigns, which have successfully eradicated nonzoonotic agents such as the variola viruses and, hopefully soon, poliovirus. This review discusses vaccines that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 74 publications
0
6
0
1
Order By: Relevance
“…The concept of live attenuated vaccines came from the Vaccinia virus, which causes cowpox in cattle but cross-protects smallpox in humans ( Riedel, 2005 ). Live-attenuated vaccine strategy is commonly and effectively used in combating viral diseases such as influenza, polio, mumps, rubella, measles, varicella, and rotavirus ( Saccente and Woods, 2010 ; Leibovitch and Jacobson, 2016 ). Such approaches have been taken to develop a vaccine against SARS-COV2 also, and it appears to be the lifesaver against COVID19 ( Sapkal et al., 2021 ).…”
Section: Candida Vaccinesmentioning
confidence: 99%
“…The concept of live attenuated vaccines came from the Vaccinia virus, which causes cowpox in cattle but cross-protects smallpox in humans ( Riedel, 2005 ). Live-attenuated vaccine strategy is commonly and effectively used in combating viral diseases such as influenza, polio, mumps, rubella, measles, varicella, and rotavirus ( Saccente and Woods, 2010 ; Leibovitch and Jacobson, 2016 ). Such approaches have been taken to develop a vaccine against SARS-COV2 also, and it appears to be the lifesaver against COVID19 ( Sapkal et al., 2021 ).…”
Section: Candida Vaccinesmentioning
confidence: 99%
“…Absence of proper treatment to neurotropic virus has strongly led to emphasis on prevention [64]. Effect of a 5-year vaccination campaign in Nepal for the prevention of Japanese encephalitis virus showed that cases of disease were reduced by 78% [65].…”
Section: Preventionmentioning
confidence: 99%
“…The first discovered and approved for human use is the 17D strain of yellow fever virus, which accumulated multiple stable and attenuating mutations throughout its genome after serial passaging in vitro . Researchers have also used 17D as a backbone to create chimeric vaccine strains for other flaviviruses, including Japanese encephalitis virus (JEV), DENV, West Nile and St. Louis encephalitis viruses, although only the first two have finished clinical trials and been approved for use in certain countries [11*, 12*, 13]. These recombinant vaccines replace the genes encoding the envelope (E) and pre-membrane (PrM) proteins of 17D with the ones from their respective viruses (the DENV vaccine includes genes for the 4 most common serotypes) [14*].…”
Section: The Foundations For Building a Zikv Vaccinementioning
confidence: 99%